Fabrication Of Thermoelectric Bismuth Telluride Films Using The Novel Resin 3d Printing Technique - Farah Liana Mohd Redzuan; Ahmad Faiz Mohammad; Shahir Yasin Mohd Yusuf; Ubaidah Syafiq; Nadhrah Md Yatim; Assayidatul Laila Nor Hairin; Ahmad Faiz Hakimi (Semarak Ilmu Sdn Bhd, 2025)
The global drive for clean energy sources to replace carbon-based fossil fuels necessitates the development of advanced fabrication processes for thermoelectric materials. Thermoelectric materials can generate electricity from ambient heat, making them promising for low-power generating devices that typically rely on batteries with limited lifespans. Compared to bulk materials, thermoelectric thin films offer enhanced performance due to increased Seebeck coefficient and reduced thermal conductivity. However, fabricating high-quality thermoelectric thin films often involves complex and costly vacuum deposition techniques, hindering their widespread application. This study explores the fabrication of thermoelectric Bismuth Telluride (Bi2Te3) films using a resin-based 3D printing method aimed at reducing synthesis costs while enhancing thermoelectric properties. Bi2Te3 films were synthesized via photopolymerization, commercially known as resin 3D printing. In this method, Bi2Te3 was mixed with a flexible photopolymer resin to facilitate film formation. Ratios of resin to Bi2Te3 tested were 60:40, 70:30, 80:20, and 90:10. As the resin content increased, the films became more durable and sturdier, despite a potential trade-off in performance. Phase analysis of the films was conducted using X-ray diffraction (XRD), confirming the presence of Bi2Te3 peaks. Elemental and microstructural characterization via Scanning Electron Microscope (SEM) revealed the presence of Bi2Te3, including pores that are potentially associated with the resin content. This study demonstrates a novel and cost-effective approach to fabricating Bi2Te3 thermoelectric films using photopolymerization 3D printing, maintaining desirable thermoelectric properties without the need for complex fabrication processes.